Development of SOA-MZI based logic gates and all-photonics flip flop - Mohd Azarulsani Md. Azidin (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2017)
The main objectives of this project are to design and simulate an XOR photonics logic gate operating in C-band region and achieving an output signal that adheres to XOR logic properties, as well as to design and simulate various SOA-MZI based logic gates all-photonics flip-flop and various SOA-MZI based logic gates. Specific objectives of this project are listed as below ; to design and simulate an XOR photonics logic gate with the configuration of TOAD, SOA-MZI using XGM and XPM nonlinear effects as well as to analyze the output of each three configurations in terms of power generated, OSNR and quality of signals (BER value) ; to design and simulate various SOA-MZI based logic gates namely AND, NOR, OR and NAND and to analyze the output signals and generated output powers ; to design and simulate an all-photonics flip-flop and to analyze the output signal running at different data rates.